Risk of Cancer in the Short and Long Term after Incident Venous Thromboembolism: The HUNT and Tromsø Studies - Langholm, Camilla; Eide, Nikolai Hagensen; Hveem, Kristian; van Es, Nick; Brækkan, Sigrid K.; Morelli, Vânia M.; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2025)
Venous thromboembolism (VTE) has long been recognized as a harbinger of cancer. The epidemiology of VTE and cancer has evolved over the past decades, and contemporary data addressing the association between VTE and subsequent risk of cancer are needed.We aimed to investigate the short- (≤1 year) and long-term (>1 year) risk of cancer after incident VTE in a population-based cohort study.A total of 111,119 participants from Tromsø4–7 (1994–2016) and HUNT2–3 (1995–2008) surveys were followed through 2020, and all first-lifetime cancer and VTE events were recorded. Cox regression was used to estimate hazard ratios (HRs) with 95% confidence intervals (CIs) for cancer diagnosis in participants with VTE compared with those without VTE, with VTE being modeled as a time-varying exposure.Among the 2,506 individuals with incident VTE, 417 had a subsequent diagnosis of incident cancer during a median follow-up after VTE of 5.2 years. In models adjusted for age (as a time-scale), sex, body mass index, smoking, and comorbidities, the HRs for cancer were 4.57 (95% CI 3.89–5.37) at 0 to 1 year, 1.19 (95% CI 0.93–1.52) at 1 to 3 years, and 1.14 (95% CI 0.99–1.31) at >3 years after overall VTE when compared with individuals without VTE, and the risk estimates were particularly pronounced at 0 to 1 year after unprovoked VTE (HR 5.63, 95% CI 4.67–6.77).Our results indicate a transient and substantially increased risk of cancer diagnosis within 1 year after an incident VTE, and especially after unprovoked VTE.
Keywords: cancer; venous thromboembolism; venous thrombosis; cohort; risk factor